ANALISIS PERAWATAN BELT MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE GUNA MENINGKATKAN PRODUKTIVITAS MESIN ATLANTIC ZEISER DI PT. WKI - Joko Prasetiyo; P. Yudi Dwi Arliyanto; Hamdani Aris Sudrajat; M. Farkhan (Politeknik Meta Industri, 2022)
Maintenance functions as monitoring, and maintaining company facilities, equipment, and work facilities by designing, managing, handling, and inspecting work to ensure functionality during uptime and minimize dowtime caused by damage or repairs.This research is used to plan machine maintenance using the Reliability Centered Maintenance (RCM) method. The purpose of this research is to plan Preventive Maintenance activities in order to improve machine reliabilility and also maintain the smooth production process. From the fishbone diagram, it is known that the belt damage on the Atlantic Zeiser engine is due to four catagories, namely Material, Method, Man, and Enviroment. The belt is often used for the production process, but selection of the belt material with good quality according to spesifications.Based on the result of the calculation of the Realibility parameter, it is obtained from the Realibility parameter that the means time between failure data, Mean Time Between Failure (MTBF) of the lowest belt component is 125 hours and Realibility is R(t) the lowest 93,801%. From the Maintainability parameter, the data obtained are the longest average maintenance time (A) for the suction Fan, which is 5,750 hours and Mean Time Between Maintenance (MTBM) is 214,000 hours. From the Availibility parameter, the data obtained are Inharen availibility (Ai) and Achieved Availibility (Aa) namely belt is 97,737% and 96,423%.Keywords : Preventive Maintenance, Belt, Reliability Centered Maintenance (RCM), Fishbone